Content and Bioaccumulation of Nine Mineral Elements in Ten Mushroom Species of the Genus Boletus. (4th June 2015) - Wang, Xue-Mei; Zhang, Ji; Li, Tao; Wang, Yuan-Zhong; Liu, Hong-Gao
Abstract : Concentrations and bioconcentration potential of nine elements (Ca, Cu, Fe, K, Mg, Mn, Na, P, and Zn) in ten species of wild edible Boletus and the corresponding underlying soils were analyzed. The analyses were performed using inductively coupled plasma atomic emission spectrophotometer. Boletus showed relative abundant contents of P, K, Fe, Mg, Ca, and Na and less of Zn, Cu, and Mn. Caps compared to stalks were enriched in P, K, Cu, Mg, and Zn, while stalks were enriched in Mn. The elements such as P and K were accumulated (BCF > 1 ), while Ca, Fe, Mg, Mn, and Na were excluded (BCF < 1 ) in the fruiting bodies. The correlation analysis indicated high correlations between Cu, Mn, Ca, and Fe in the mushrooms as compared to the corresponding soils. Significant correlations were also obtained between Cu-P (r = 0.775 ), Fe-P (r = 0.728 ), and Zn-P (r = 0.76 ) for caps and Cu-Mg (r = 0.721 ), Fe-Mg (r = 0.719 ), Zn-Mg (r = 0.824 ), and Zn-P (r = 0.818 ) for stalks. The results of this study imply that ability of fungi to accumulate elements from substrate could be influenced by mushroom species and underlying soil substrates.